Taj Mahal Lovers' Story - Devji, Mantoshe Singh (Two Lions, 1997)
From the recesses of the divine mind arises an immortal force which drives the soul of the lover and blends with the beloved's soul and being,to leave an astonished world wondering and gasping at the power and beauty of eternal love.
Keywords: Fiction; General, History